The impact of fiscal policy and trade liberalization on Jordan's economic growth - Al-kasasbeh, Omar
The issues of economic growth have been debated immensely in all over countries. Likewise, Jordan has long sought to improve its economic growth by reforming the fiscal policy and trade liberalization to achieve sustainable economic growth. However, Jordan has been experiencing volatility in economic growth over the years. Therefore, the main objectives of the study are: 1) to determine the long-run and short-run relationship between taxes, government expenditure, public debt, trade liberalization and economic growth in Jordan; 2) to examine the dynamic causality between taxes, government expenditure, public debt, trade liberalization and economic growth in Jordan; 3) to identify the impact of financial crises on economic growth in Jordan; 4) to assess the responsiveness of economic growth to changes on taxes, government expenditure, public debt and trade liberalization in Jordan. This study employed Augmented Dickey-Fuller (ADF) unit root test, Philipps-Perron (PP) unit root test, Zivot Andrews (A.Z) unit root test, Kapetanios (K) unit root test with a structural break, Autoregressive Distributive Lags (ARDL) Bound cointegration test, Maki cointegration test with tructural break, Granger causality test and Bayesian Vector Autoregressions (BV AR). The results of both ARDL co integration test and Maki cointegration test revealed that long-run co integration exists between taxes, government expenditure, public debt, trade liberalization and economic growth. In addition, the result of ARDL long-run estimates showed that taxes, government expenditure, trade liberalization have positive and significant effects on economic growth. Additionally, public debt indicates a significant negative effect on economic growth. However, the 1989 Jordanian crisis has significant negative effect on economic growth. Besides, the 2008 financial crisis has positive effect on economic growth. Furthermore, the results of Granger causality test indicated that there is a bi-directional causality between government expenditure and economic growth. Moreover, the result also showed unidirectional causal relationship from economic growth to public debt and trade liberalization, and from taxes to economic growth. On top of that, the result of impulse response and variance decomposition disclosed that government expenditure and public debt is the most important variables of influencing the economy in Jordan. The efforts by Jordan government should be directed in creating an economic environment with a peaceful political climate and financial discipline. They should also provide adequate taxes reforms as there is a need to enhance trade balance through increasing Jordanian exports as much as possible. Besides, the government should prioritize Jordan investment needs in infrastructure projects and public services.